2007
DOI: 10.1002/ps.1424
|View full text |Cite
|
Sign up to set email alerts
|

Biological control of terrestrial molluscs usingPhasmarhabditis hermaphrodita—progress and prospects

Abstract: Phasmarhabditis hermaphrodita Schneider (Nematoda: Rhabditidae) is a nematode that parasitises a wide range of slug and snail species. It has been formulated into a biological control agent (Nemaslug) and was commercialised in 1994. It is now available in fourteen European countries. A review is given of all research on P. hermaphrodita, including basic biology, mass cultivation, formulation, host range, application strategies, field efficacy and effects on non-target organisms. The many critical gaps in prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
137
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(144 citation statements)
references
References 77 publications
(101 reference statements)
4
137
3
Order By: Relevance
“…This observation suggests that, unlike EPNs (Yang et al, 1997), P. hermaphrodita can produce full quality DJs on a variety of substrates including plant tissue. This fact is in accordance with the saprobic lifestyle of P. hermaphrodita (MacMillan et al, 2009;Rae, Verdun, Grewal, Robertson, & Wilson, 2007).…”
Section: Discussionsupporting
confidence: 86%
“…This observation suggests that, unlike EPNs (Yang et al, 1997), P. hermaphrodita can produce full quality DJs on a variety of substrates including plant tissue. This fact is in accordance with the saprobic lifestyle of P. hermaphrodita (MacMillan et al, 2009;Rae, Verdun, Grewal, Robertson, & Wilson, 2007).…”
Section: Discussionsupporting
confidence: 86%
“…10) Our results also support previous findings by Wilson et al 9) about the optimum population growth temperature range of P. hermaphrodita, which is between 12 and 18°C, since in the WW plots, the mean daily minimum and maximum temperatures were 11.3°C and 16.2°C, respectively, within a range of extreme values of 10.1 and 18.5°C. In the NW plots, the mean daily minimum temperature was 6°C, with an extreme value of 2.2°C, and it has been shown that the reproduction of P. hermaphrodita decreases significantly below 10°C.…”
Section: Discussionsupporting
confidence: 92%
“…The significant interaction between climate treatment and nematode presence/ absence in both slug damage and slug numbers suggests that an increased mean winter temperature in the range of 4.0-4.5°C, as predicted for NW Spain, might improve the performance of P. hermaphrodita as a slug biocontrol agent during the winter. Early inhibition of slug feeding following infection by P. hermaphrodita is considered a key factor in the success and rapid action of the nematode as a biocontrol agent, 6,10) and this aspect of the interaction between P. hermaphrodita and D. reticulatum seems to have benefited from the winter warming conditions of the experiment: 3 days after the introduction of slugs into the trays, there were no differences between treatments in slug numbers, while slug damage was significantly lower in the nematode-treated plots under WW conditions than under NW conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another much less studied nematode that is sold throughout Europe as a biological control agent is the slug parasite, Phasmarhabditis hermaphrodita (Rae et al, 2007), under the tradename Nemaslug Ò . This nematode shares many similarities with entomopathogenic nematodes in that it forms dauer juveniles that infect slugs.…”
Section: Introductionmentioning
confidence: 99%